(untitled) - Zeithaml, Valarie A. (Boston, 2006)
Services Marketing, 4/e, by Zeithaml and Bitner provides a comprehensive review and analysis of services marketing issues, practice, and strategy. Utilizing the GAPS Model of Service Quality as an organizing framework the structure of the text offers part openers that sequentially build the model gap by gap. Each part of the book includes multiple chapters with strategies for understanding and closing the critical gaps. Customer behavior, expectations, and perceptions are discussed early in the text to form the basis for understanding services marketing strategy and the managerial content, in the rest of the text, is framed by the GAPS model. Additionally, the authors continue to refine conceptual frameworks for developing effective services marketing strategy and have incorporated more coverage of the use of technology and business-to-business applications in this edition
Keywords: Service industries,Customer services,Marketing,Công nghiệp dịch vụ,Dịch vụ khách hàng,Tiếp thị; Marketing,tiếp thị,tiếp thị